Hypoglycemic and Hypolipidemic Effects of Mimusops elengi Linn Extracts on Normoglycaemic and Alloxan-Induced Diabetic Rats - Zahid, Hina (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACTTo evaluate the hypoglycemic effect of methanolic extracts of flower and leaves of Mimusops elengi Linn (Sapotaceae) in normoglycaemic and alloxan-induced diabetic rats. Both extracts of Mimusops elengi Linn were administered orally (100 mg/kg, body weight) to normal and alloxan-induced diabetic rats. The fasting blood glucose (FBG), oral glucose tolerance test (OGTT) and alloxan-induced diabetic models were performed for the hypoglycemic effects and compared with tolbutamide (100 mg/kg, body weight), a standard drug. Both the extracts (MFE and MLE) showed marked decreased (P < 0.01) in blood glucose level in normotensive rats within 2 h after oral administration. A significant (P < 0.001) decreased in elevated blood glucose level was observed in glucose loaded animals. The onset of action of action in glucose tolerance test (OGTT) was 30 min. MFE and MLE significantly (P < 0.01) decreased blood glucose level from 221.83±3.73, 210.50±2.51 to 157.00±9.89, 173.33±11.21 mg/dl respectively after 7 days treatment in alloxan-induced diabetic rats. MFE and Tolbutamide in treated animals showed significant (P < 0.001) improvement of body weight up to 5.24 %, 3.35% respectively. In diabetic rats, MFE and MLE treatment at a dose of 100 mg/kg, body weight for 7 days significantly (P < 0.01) decreased triglycerides levels compared to the diabetic control group. The present study demonstrated the potential hypoglycemic and hypolipidemic effects of flower and leaves of Mimusops elengi Linn and support the traditional use of the plant as hypoglycemic and hypolipidemic agents.